Tunisia : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1996)
This paper reviews economic developments in Tunisia during 1990-95. Despite adverse exogenous developments, including the Middle East crisis, weak economic growth in key European export markets and a severe drought, Tunisia achieved a strong economic performance during 1991-95. Real GDP growth rose to an annual average of 4.2 percent, resulting in an increase in per capita income of some 2 percent per year. Inflation fell from an average of 7 percent during the preceding five years to 5.8 percent during 1991-95.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet